(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
In this interview, Thomas Tufte explores the concept of Buen Vivir, originated from Andean indigenous cultures, and highlights its complexity and variations in Latin America and Europe. He emphasizes the importance of the dialogue of knowledge and the creation of spaces of trust to promote communication for social change, underscoring the crucial role of communities in this process. Tufte also addresses the need to strengthen community communication to combat inequalities in the media. Furthermore, he discusses the influence of mainstream media, its opportunism in relation to the market, and the importance of legislation to ensure a more equitable media landscape. Tufte acknowledges the potential of digital platforms to amplify voices but warns against the commercial logics of large corporations, emphasizing the need for digital education and proper regulation. From a post-pandemic perspective, he sees opportunities for change, especially through the involvement of social movements, while highlighting the climate crisis as a new challenge. Regarding participatory communication, he considers it more than just a tool but an objective in itself, relating it to the pedagogy of Paulo Freire. Tufte also suggests that discussions about development and social change should begin with the desired society, emphasizing the importance of pluralism and flexibility in approaching communication and social change.